Ganti Rugi Sebagai Wujud Kepastian Hukum Terhadap Barang Rusak Akibat Kebakaran Dalam Pengiriman Cargo - Christalia, Wanda; Sutrisno, Sutrisno (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2025)
The implementation of compensation for goods damaged due to fire during the transportation of goods at the J&T Cargo Banyuwangi shipping service company is based on a transportation agreement that has been agreed upon by the parties who have reached an agreement. This transportation agreement is binding between both parties who have their respective rights and obligations. This research aims to determine the implementation of compensation for damaged goods in transportation at the J&T Cargo Banyuwangi delivery service company and to determine the obstacles in implementing compensation for damaged goods in transportation at the J&T Cargo Banyuwangi delivery service company. The type of research used is empirical juridical legal research with a statutory approach to the problems raised by the author. The results of the research show that in the implementation of compensation for damaged goods in the transportation of goods at the J&T Cargo Banyuwangi delivery service company, the implementation has been carried out well in accordance with applicable regulations, but in the implementation there are sometimes still negotiations regarding the nominal amount of compensation.